"Eco-tool-seeker": A new and unique business guide for choosing ecodesign tools. (10th May 2017) - Rousseaux, Patrick; Gremy-Gros, Cécile; Bonnin, Marie; Henriel-Ricordel, Catherine; Bernard, Pierrick; Floury, Léa; Staigre, Gwenaëlle; Vincent, Philippe
Abstract: Environmental sustainability has emerged as a key issue amongst governments, policymakers, researchers, companies and the general public. In Europe, governments are trying to encourage companies to integrate ecodesign into their processes. A great variety of ecodesign tools exists but the actual implementation level of such tools remains limited or not successfully integrated throughout the different company processes. Having identified the main barriers to ecodesign implementation, this article provides a literature review of the existing tools that can be used in various company departments. From this review, 629 tools were found and characterized. Taxonomy was established to classify these tools into 22 categories of ecodesign tools and 5 departments in companies. These tools are classified as normative or non-normative which can be generic or sectorial as well as "environmental" or "improvement". A guide (or information system) has been then developed to help companies to choose ecodesign tools for three targets: production, management or communication. The proposed guide can also be useful for researchers, teachers, and trainers. In order to facilitate these choices, a free computerized version of this guide, called "Eco-tool-seeker", has been developed. Graphical abstract: Highlights: This paper provides the first taxonomy in the field of eco-design and a "mega-compilation" of629 eco-design tools. A guide was developed to implement ecodesign in companies and to assist them in identifying ecodesign tools. A friendly and free version of the guide is available on Internet.